The influence of the consumer perceived value on the satisfaction with the grocery retailer relationship: the mediating effect of the risk of unsustainable consumption - Menezes, J. (2014)
This paper proposes a framework to analyse the influence of the different dimensions of the perceived value on consumer satisfaction with the grocery retailer relationship. The research propositions consider, as a mediating effect, the perceived unsustainable consumption risk associated to the purchase. Indeed, it is expectable that the perception, by consumers, of an existing risk of unsustainable consumption, will influence the subsequent perceived satisfaction with the benefits. The research propositions were supported by the literature review on sustainable consumption and consumer perceived value, according to the relationship marketing knowledge.